Characterization and Evaluation of Soil Erosion in Shenzhen: Using Environmental Radionuclides - Li, Ding Qiang; Li, Jun Jie; Zhuo, Mu Ning (Applied Mechanics and Materials, 2014)
Nuclear tracer technology is quantitative and it has a high priority, which provides a unique method for understanding the mechanism of urban soil and water loss. 137Cs + 210Pbex combination tracer was applied to study the characterization and evaluation of soil Erosion in Shenzhen. The results indicate that the following: 1)Disturbances from urbanization has greatly changed surface soil in Shenzhen.137Cs background inventory in Shenzhen range at 99 Bq/m2-653 Bq/m2. 2)210Pbex background inventory increase with altitude rise, which is attributed to the movement of water vapor. 3)Soil erosion in Shenzhen has a wide distribution area and exacerbated by severe human disturbance. Land development and steep orchard are key factors that influence urban soil and water loss. 4)Shenzhen should strictly carry out projects for soil and water conservation, such as returning steep slopes into forests and grasslands, and other ecological management reforms.